Monitoring through many eyes: Integrating disparate datasets to improve monitoring of the Great Barrier Reef. (February 2020) - Peterson, Erin E.; Santos-Fernández, Edgar; Chen, Carla; Clifford, Sam; Vercelloni, Julie; Pearse, Alan; Brown, Ross; Christensen, Bryce; James, Allan; Anthony, Ken; Loder, Jennifer; González-Rivero, Manuel; et al.
Abstract: Numerous organisations collect data in the Great Barrier Reef (GBR), but they are rarely analysed together due to different program objectives, methods, and data quality. We developed a weighted spatio-temporal Bayesian model and used it to integrate image-based hard-coral data collected by professional and citizen scientists, who captured and/or classified underwater images. We used the model to predict coral cover across the GBR with estimates of uncertainty; thus filling gaps in space and time where no data exist. Additional data increased the model's predictive ability by 43%, but did not affect model inferences about pressures (e.g. bleaching and cyclone damage). Thus, effective integration of professional and high-volume citizen data could enhance the capacity and cost-efficiency of monitoring programs. This general approach is equally viable for other variables collected in the marine environment or other ecosystems; opening up new opportunities to integrate data and provide pathways for community engagement/stewardship.